Closed-Loop Control System Design for Wireless Charging of Low-Voltage EV Batteries with Time-Delay Constraints - Viktor Shevchenko; Bohdan Pakhaliuk; Janis Zakis; Oleksandr Veligorskyi; Jaroslaw Luszcz; Oleksandr Husev; Oleksandr Lytvyn; Oleksandr Matiushkin (Energies, 2021)
This paper presents an inductive power transfer system on the basis of a double single-phase three-level T-type inverter and two split transmitting coils for constant current and constant voltage wireless charging of low-voltage light electric vehicle batteries with closed-loop control, considering time-delay communication constraints. An optimal control structure and a modified control strategy were chosen and implemented to the wireless power transfer system as a result of a review and analysis of existing solutions. The control system analysis and adjustment of the coefficients of the regulator using Laplace transform were performed. Our study addressed the behavior of the control system with different time delays as well as the dynamic response of the system. The detecting algorithm of a secondary coil was proposed, which ensured efficient system operation and increased the functionality, safety and usability of the device. The efficiency of energy transfer of 90% was reached at the transmitted power of 110 W, which is at the level of existing solutions considered in the article and opens the way to the commercialization of the proposed solution. Therefore, the feasibility of using a nonclassical multilevel inverter, together with split transmitting coils for wireless charging was confirmed.